Optimizing Land Utilization and Planting Season Cycles in Noelbaki Village, Kupang Tengah District - Melania Priscilla Natun; Hamza H. Wulakada; Arfita Rahmawati (Tinta Emas Institute, 2025)
This study aims to: (1) map farmers' cropping patterns in the growing season cycle in Noelbaki Village; (2) identify internal-external factors of land use through the SWOT framework and the IFAS-EFAS matrix; and (3) formulate land intensification strategies appropriate to local conditions. The approach used is a mixed methods approach, combining descriptive qualitative analysis and quantitative SWOT analysis. Data were collected through observation, interviews, documentation, questionnaires, and focus group discussions (FGD). Analysis was carried out by mapping cropping patterns, compiling IFAS-EFAS to obtain total strengths-weaknesses and opportunities-threats, and determining positions in the SWOT quadrants as a basis for recommendations. The results show that farmers generally implement a rotational cropping pattern with two rice seasons per year, interspersed with vegetable commodities during the break period. Key strengths include soil fertility, farming experience, and irrigation support; weaknesses include low technology adoption and high production costs. Opportunities arise from government program support, access to technology, and increasing market demand, while the main threats are seasonal shifts and pest attacks. Priority strategies include the use of superior seeds, strengthening irrigation systems, diversifying crops based on local agroecology, and accelerating the adoption of modern agricultural technologies.